Liberal vs restrictive concept of the EU immigration policies - Maksimović, Andrijana; Milosavljević, Zoran (Serbian Journal of Management, 2022)
The authors of the paper deal with the immigration policies in the European Union, i.e. in its member states as constituent parts of a complex community. The main aim is to determine what immigration policies are conducted by the EU member states depending on their public opinion, their social, demographic, and economic structure, as well as cultural, political-parliamentary and security policies. It is assumed that the immigration policies of the EU member states could be researched on an ideal-type scale, ranging from liberal to restrictive immigration policies. Based on all available quantifiers, we opted for MIPEX or the Migrant Integration Policy Index. Based on MIPEX, one can clearly see the tendency towards one of the borderline immigration policies on a scale ranging from liberal to restrictive immigration policies. The EU member states whose nationality is territorially bounded, (nation states, the civil-national principle) and which have long immigration tradition tend to opt for liberal immigration policies. Institutional measures such as allocating funds for welfare benefits and government efficiency point out to stable systems of welfare state where liberal immigration policy is dominant. In addition, communities which are economically strong and stable in terms of security, also show tendencies towards liberal immigration policy.